Density functional theory study of azobenzene derivatives as potential materials for wettability switching - Adyrbekova, G.; Saidakhmetov, P.; Burganova, R.; Piyanzina, I.; Baiman, G.; Baubekova, G.; Tayurskii, D. (Karagandy University of the name of academician E.A. Buketov, 2025)
In this study, density functional theory (DFT) is employed to analyze the properties of 16 azobenzene derivatives, assessing their potential as wettability switching materials. Inspired by K. Ichimura’s 2001 report on azobenzene-modified surface wettability, we explore the impact of photoisomerization-induced changes in molecular dipole moments between cis and trans configurations of different azobenzene derivatives. In parent azobenzene molecule this process transforms non-polar molecule into a more hydrophilic cis form. The control of surface wettability holds immense potential across diverse domains, such as industry, medicine, microbiology, electronics, and materials science. By harnessing this control, we can unlock the potential to create innovative materials, elevate functionality, and boost efficiency. It enables to enhance product performance, improve adhesion, and achieve precision in liquid handling. Our investigation delves into the structural, electronic, and molecular aspects of all studied molecules utilizing the hybrid B3LYP functional with DFT-D3 dispersion correction and a 6-31++G(d, p) basis set, presenting promising azo-type structures for surface wettability manipulation. Two azobenzene derivatives emerge as potential candidates, exhibiting transformations during cis-trans photoisomerization — one towards increased hydrophilicity and the other in the opposite direction.
Keywords: azobenzene derivative; wettability switching; photoisomerization; dipole moments; cis-trans configurations; DFT; B3LYP functional; 6-31++G(d, p) basis set; photoswitchable materials; hydrophilicity